Determinasi Konsentrasi Kepemilikan dan Tipe Kepemilikan terhadap Kinerja dan Risiko Perbankan di Indonesia: The Determination of Concentration and Type of Ownership on Bank Performance and Risks in Indonesia - Yacobo P Sijabat; Michael Jeffri Sinabutar; Heni Hirawati; Axel Giovanni (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2020)
This research aims to examine the determination of concentration and type of ownership on the performance and risks of banks listed on the Indonesia Stock Exchange (IDX) for the period 2000-2018. This research was quantitative research using panel data regression analysis methods. The main characteristic of panel data regression analysis is the use of the Hausman test. Data were obtained and collaborated from several data providers such as Osiris, Bloomberg, and the Financial Services Authority (Otoritas Jasa Keuangan or OJK) website. Secondary data were collected from 42 banks listed on the Indonesia Stock Exchange (IDX) using a purposive sampling technique. The data was processed using Stata software. The ownership concentration was measured using the Herfindahl-Hirschman Index (HHI) and foreign and domestic ownership as the proxy using the dummy variable. To measure bank performance, this research was used ROA and ROE proxy while the standard deviation of returns was used to measure bank risks. The results of the research showed that there was no effect of ownership concentration on bank performance. Also, domestic ownership has a positive effect on bank performance. In terms of risks, ownership concentration has a positive effect on bank risks. The more concentrated the ownership of the bank, the bank will more at risks. Besides, foreign and domestic ownership affects bank risks. Foreign ownership has a positive effect on bank risks. The level of foreign ownership of the bank affects bank risks. High foreign ownership puts the bank at risk.